2015
DOI: 10.4067/s0301-732x2015000300002
|View full text |Cite
|
Sign up to set email alerts
|

Potential of condensed tannins for the reduction of emissions of enteric methane and their effect on ruminant productivity

Abstract: Potencial de los taninos condensados para reducir las emisiones de metano entérico y sus efectos en producción de rumiantes RESUMENEl metano (CH 4 ) es un gas subproducto de la fermentación de los carbohidratos en el rumen. La agricultura contribuye con el 47% de las emisiones antropogénicas de CH 4 , siendo los rumiantes responsables del 39% de las emisiones de metano entérico. Este gas de efecto invernadero (GEI) tiene un potencial de calentamiento global 25 veces más que el CO 2 y representa una pérdida de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 57 publications
0
27
0
6
Order By: Relevance
“…Only results of Animut et al (2008b) suggested that negative effects of CT on activity of non-methanogenic bacteria, particularly fibrolytics, to lessen hydrogen availability to methanogens and indirectly lessen methane production. Findings of studies of Animut et al (2008aAnimut et al ( , 2008b were strongly indicative and some of Puchala et al (2012b) and the Puchala et al (2012a) experiment with fresh forage were somewhat supportive of decreased methane emission via direct effects of CT on the number and (or) activity of protozoa, thus with indirect effect by impacting hydrogen availability to symbiotic methanogens in physical association with methanogens (Piñeiro-Vázquez et al 2015;Tapio et al 2017). Hence, it is conceivable that effects of supplemental concentrate in the present experiment on the number and(or) activity of protozoa influenced impact of lespedeza CT on ruminal methane emission, and the same is possible for effects of monensin, coconut oil, and soybean oil as well.…”
Section: Methanementioning
confidence: 88%
“…Only results of Animut et al (2008b) suggested that negative effects of CT on activity of non-methanogenic bacteria, particularly fibrolytics, to lessen hydrogen availability to methanogens and indirectly lessen methane production. Findings of studies of Animut et al (2008aAnimut et al ( , 2008b were strongly indicative and some of Puchala et al (2012b) and the Puchala et al (2012a) experiment with fresh forage were somewhat supportive of decreased methane emission via direct effects of CT on the number and (or) activity of protozoa, thus with indirect effect by impacting hydrogen availability to symbiotic methanogens in physical association with methanogens (Piñeiro-Vázquez et al 2015;Tapio et al 2017). Hence, it is conceivable that effects of supplemental concentrate in the present experiment on the number and(or) activity of protozoa influenced impact of lespedeza CT on ruminal methane emission, and the same is possible for effects of monensin, coconut oil, and soybean oil as well.…”
Section: Methanementioning
confidence: 88%
“…How does the presence of other forage compounds (carbohydrates and lipids) effect CT-protein interactions and precipitation. There have been a number of studies conducted on how CTs affect rumen bacteria and protozoa populations (McSweeney et al, 2001;Sivakumaran et al, 2004;Smith et al, 2005;Benchaar et al, 2008;Tan et al, 2011;Piñeiro-Vázquez et al, 2015) and biohydrogenation (Khiaosa-Ard et al, 2009;Vasta et al, 2009;Costa et al, 2017). Some research has been conducted on how carbohydrates present in the digesta may affect CT-protein complex formation and utilization Liang et al, 2013;Barros et al, 2014).…”
Section: The Path Forward: Questions To Addressmentioning
confidence: 99%
“…Gerlach et al (2018a) did not observe any effect of tannins on the digestibility of the concentrate OM when the tannin content was 1%, but it reduced drastically when the content was 3% (À21%) and 5% (À28%). The effect of tannins on reducing DMI is generally by rumen physical filling and is attributed to the fact that tannins depress fibre digestion by forming complexes with lignocellulose and hence prevent microbial digestion (Piñeiro-V azquez et al 2015), either by direct inhibition of cellulolytic microorganisms or fibrolytic enzymatic activity or both (Patra and Saxena 2011).…”
Section: Introductionmentioning
confidence: 99%
“…There appear to be no studies which evaluated the possibility of interaction between monensin and tannins in ruminants. Although they have different mechanisms of action, these additives separately reduce rumen protein degradability (Russel and Strobel 1989;Ruiz et al 2001;Piñeiro-V azquez et al 2015;Addisu 2016). Some authors such as Seo et al (2010) report that the high rate of rumen protein degradation reduces the efficiency of protein utilisation because there is generally no simultaneous availability (synchronisation) of enough energy for microbial protein synthesis.…”
Section: Introductionmentioning
confidence: 99%